Thermal, precipitation and hydrological conditions in the Natura 2000 Puszcza Białowieska area in the context of ongoing climate change - Wałek, Grzegorz; Suligowski, Roman (Acta Geographica Lodziensia, 2024)
The paper presents changes in thermal and precipitation conditions in the Puszcza Białowieska Natura 2000 area and the differences in river runoff in two streams (Narewka, Leśna) flowing through this area. The analysis of the course of selected climate elements and hydrological characteristics was based on long-term (minimum 60-year) observation sequences. The research results indicate: an increase in the average annual and seasonal air temperatures, a growing trend in the annual number of hot days and annual precipitation totals, a clear increase in the average annual values of the precipitation intensity index and a decreasing number of days with snow cover. The features of the river regime are also changing. A downward trend in average annual and monthly (except January and February) runoff, a shift in the spring culmination of runoff, and an acceleration of the occurrence of summer low flows are observed. These phenomena are unfavorable from the point of view of the stability of ecosystems and plant communities within the studied Natura 2000 area.